PENGARUH PENDIDIKAN, PELATIHAN, GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA CV KEMUNING PRIMA ILMU - Setyanto, Eddy; Taufik Hidayat, R (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
Employee performance is a key factor in an organization's success, influenced by various elements such as education and training, leadership style, and motivation. This study aims to analyze the combined impact of these factors on employee performance at CV Kemuning Prima Ilmu , a company specializing in training and educational consulting. Using a quantitative approach with multiple regression analysis, this research evaluates data collected through surveys of CV Kemuning Prima Ilmuemployees. The analysis results indicate that education and training have a significant impact on employee performance, with a regression coefficient of -0.2194 and a p-value of 0.024, suggesting that improvements in education and training can lead to changes in employee performance. Leadership style has a regression coefficient of -0.0532 with a p-value of 0.589, indicating that this variable does not significantly affect employee performance. Meanwhile, motivation has a significant impact on performance, with a regression coefficient of -0.2310 and a p-value of 0.021, demonstrating a complex relationship between motivation and employee performance. These findings emphasize that a holistic approach combining continuous education and training, inspirational leadership, and appropriate motivational strategies can significantly enhance employee performance. The implications of this study provide valuable insights for organizations in designing more effective human resource development strategies to achieve sustainable business goals.